(untitled) - Chang, Tien-Chien (Englewood Cliffs, N.J., 1998)
This book focuses on the science, mathematics and engineering of these new engineering methods.
Keywords: Computer integrated manufacturing systems.,CAD/CAM systems,Flexible manufacturing systems; Tin học trong sản xuất